The right to education and attitudes toward Hijras in Bangladesh: assessing educational support to achieve sustainable communities - Abul Kalam; Md Jahangir Alam; Lubaba Basharat; Golam Faruk Sarker; M. Abdullah Al Mamun; Abu Hossain Muhammad Ahsan (Quality Education for All)
Purpose – This study aims to evaluate the current educational opportunities available to hermaphrodite (Hijra) students, analyze their difficulties while pursuing academic degrees and suggest potential approaches to address these issues. Design/methodology/approach – This research used a qualitative method to analyze the challenges Hijra individuals face in pursuing education. A total of 20 interviews were conducted with two Hijra groups those who are pursuing an education and those who have abandoned it to collect primary data. The purposive sampling technique was used to identify and choose diverse sources of information. Moreover, the phenomena have been comprehended using the Access Theory and the Gender Stratification Theory. Findings – The findings show that although every Bangladeshi has the right to a decent education, few Hijra youngsters attend schools. Numerous barriers, such as discriminatory views and remarks about third-gender people, physical and mental harassment, a lack of emotional and financial support, family issues, discrimination in the school community and hostility from classmates and teachers, make it difficult for hermaphrodite students to receive a proper education. Originality/value – This research paper fills a gap in the current body of knowledge by presenting empirical evidence regarding young people’s perceptions of the third-gender, the societal barriers faced by Hijra individuals in their pursuit of quality education, their future opportunities, the root causes of these challenges and possible solutions.